THE QUALITY CHARACTERISTICS OF KATSUOBUSHI LITTLE TUNA (Euthynnus affinis) PROCESSED BY USING LIQUID SMOKE PYROLYZED FROM VARIED SMOKE SOURCES - Fitriani, Hotma; Mus, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study about the quality characteristics of katsuobushi little tuna (Euthynnus affinis) processed by using liquid smoke pyrolyzed from varied smoke sources was conducted in Februari – April 2016. This study was intended to best quality varied liquid smoke source of processed little tuna katsuobushi. The quality parameters of this study were the sensory quality included the value of appearance, smell, and texture; chemical characteristics, included pH, moisture, ash, and phenol content; and microbiologic characteristics, included total bacterial colonies, identification of bacteria Salmonella sp, Staphylococcus aureus, and fungi. The experimental design was Completely Randomized Design (CRD) and the treatment applied was of the different smoke sources, namely coconut shell (A1), coconut husk (A2) and empty pulm fruit bunch (A3). The fish fillet was soaked in the liquid smoke at the concentration of 8% for 60 minutes. The results showed that the liquid  smoke of the coconut shell (A1) was producing the best quality of little tuna katsuobushi.The characteristic of appearance is clean, shiny color without cracks, on the surface area of katsuobushi was fully fungi of yield (Aspergilus sp), spesific smell katsuobushi without additional odor, hard texture not easly broken. The katsuobushi contained of moisture 7,66 %, ash 0,67%, phenol 3,216 ppm, the value of pH 6,68, and total bacterial colonies 1,29x103cfu/g. The existence of bacteria Salmonella sp and Staphylococcus aureus was negative and the type of fungus grown on all used materials liquid smoke was Aspergillus sp. Keywords: katsuobushi, little tuna, liquid smoke